REDUCTION OF ACEH'S INCOME INEQUALITY BY THE CONTRIBUTION OF THE FISHERIES, AGRICULTURE AND FORESTRY SECTORS - Agus Naufal; Wiwiek Rindayati (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
The aimed of this study is to determine the dynamics of income inequality in Aceh and the role of the fisheries, agriculture and forestry sector (FAF) in reducing income inequality in Aceh. The method used to find income inequality using the Williamson index, while to find the role of the FAF sector in reducing income inequality is to compare the Williamson index by including the FAF sector and without including the FAF sector. The results of the analysis show that there has been a dynamic of regional income inequality in Aceh which is decreasing. After the analysis, it is seen that income inequality will increase if the GDP of the FAF sector is excluded from the count. These results are reinforced by the results of the analysis of a strong negative correlation between GRDP of the FAF sector and the Inequality Index, which means that an increase in the contribution of the FAF sector will reduce the income inequality that occurs. The two-mean paired test also strengthens the evidence that the Inequality Index by including the FAF sector GRDP in the calculation is smaller than the Inequality Index without including the FAF sector GRDP.